A RECYCLED-ART MiSSiON - Miller, Shannon McClintock; Hoena, Blake; Brown, Alan (North Mankato, Minnesota: STONE ARCH BOOKS, 2019)
"When you have a problem, where can you go for answers? The library! When Matt has an assignment that he can't figure out, he and his friends join Ms. Gillian, the Specialist, on another Adventure in Makerspace. Will the famous artist Picasso help them make art out of junk? Join them to complete A Recycled-Art Mission!"--
"A 4D book"--Back cover.
Ages 8-10
Keywords: Found objects (Art) -- Juvenile literature; Handicraft -- Juvenile literature; Recycling -- Juvenile literature; Makerspaces -- Juvenile literature; Found objects (Art) -- Comic books, strips, etc